New perspectives on young children's moral education developing character through a virtue ethics approach - Eaude, Tony (Bloomsbury Academic, 2016)
"New Perspectives on Young Children's Moral Education explores how to approach young children's moral education in a world of uncertainty and change" -- Provided by publisher.